PENGARUH SELF ASSESSMENT SYSTEM, PEMERIKSAAN PAJAK, DAN PENAGIHAN PAJAK TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI (PPN) PADA KPP PRATAMA BANDA ACEH - Cut Inayatul Maulida; Adnan Adnan (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
The purpose of this study is to describe how self assessment system, tax audit, and tax collection on value added tax (VAT). The population in this study are taxpayers of individuals and entities within the scope of KPP Pratama Banda Aceh. Data is collected  by documentation technique. The data used are data obtained from the documentation of KPP Pratama Banda Aceh. The influence of independent variable to dependent variable is done by using multiple linear regression model. The results of this study indicate that partially self assessment system and tax audit have no effect on value added tax (VAT) while tax collection has an effect on Value Added Tax (VAT) at KPP Pratama Banda Aceh. While simultaneously, self assessment system, tax audit, and tax collection have an effect on Value Added Tax (VAT) at KPP Pratama Banda Aceh.